2019
DOI: 10.3390/cancers11121968
|View full text |Cite
|
Sign up to set email alerts
|

The Chalcone Lonchocarpin Inhibits Wnt/β-Catenin Signaling and Suppresses Colorectal Cancer Proliferation

Abstract: The deregulation of the Wnt/β-catenin signaling pathway is a central event in colorectal cancer progression, thus a promising target for drug development. Many natural compounds, such as flavonoids, have been described as Wnt/β-catenin inhibitors and consequently modulate important biological processes like inflammation, redox balance, cancer promotion and progress, as well as cancer cell death. In this context, we identified the chalcone lonchocarpin isolated from Lonchocarpus sericeus as a Wnt/β-catenin path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 48 publications
(40 reference statements)
0
32
0
Order By: Relevance
“…The azoxymethane/dextran sodium sulfate (AOM/DSS) mouse model stands as a relevant preclinical inflammation-associated CRC model with histological and phenotypic features. AOM/DSS simulates the physiological and pathological process of cancer induced by chronic intestinal inflammation, and therefore, it has been widely used to study the formation mechanism of inflammation-related cancer ( 15 , 16 ). The purpose of this study was to study the antitumor effect of a microecological preparation, JK5G, by constructing the tumor model.…”
Section: Introductionmentioning
confidence: 99%
“…The azoxymethane/dextran sodium sulfate (AOM/DSS) mouse model stands as a relevant preclinical inflammation-associated CRC model with histological and phenotypic features. AOM/DSS simulates the physiological and pathological process of cancer induced by chronic intestinal inflammation, and therefore, it has been widely used to study the formation mechanism of inflammation-related cancer ( 15 , 16 ). The purpose of this study was to study the antitumor effect of a microecological preparation, JK5G, by constructing the tumor model.…”
Section: Introductionmentioning
confidence: 99%
“…28 And growing researches suggested that wnt/β-catenin was involved in the growth and metastasis of tumor cells. [29][30][31] As well, activation of wnt/ β-catenin pathway was found in glioma cells, and blocking of wnt/β-catenin pathway suppressed multiple oncogenic targets. 32 In our study, forced expression of FGD5-AS1 activated wnt/β-catenin pathway with a dramatic change of β-catenin and cyclin D1.…”
Section: Discussionmentioning
confidence: 99%
“…IEC-6 cells have been widely used in the study of intestinal mucosal repair [22]. Scholars have conducted in-depth and systematic research on the physiological regulation [23], signaling pathways [24] and pathology [25] of intestinal mucosal injury, but there have been few reports of drugs to repair the gastrointestinal mucosa. This study demonstrated that GE can promote the migration of IEC-6 cells and reduce LPSinduced damage and has a protective effect on IEC-6 cells.…”
Section: Discussionmentioning
confidence: 99%